Historical Trauma: Literary and Testimonial Responses to Hiroshima - Ghonim, Mariam (AUC Knowledge Fountain, 2023)
The concept of trauma is controversial in literature. While one may be able to come up with ways to describe trauma in fiction, representing historical trauma is a hard task for writers. Some argue that trauma can not be described through those who did not experience it, while others claim that, provided some elements are added, one can represent trauma to the reader. This thesis focuses on twentieth-century historical traumas related to a nuclear catastrophe and explores the different literary and testimonial responses to the catastrophic man-made event of Hiroshima (1945). In this thesis, Kathleen Burkinshaw’s historical fiction The Last Cherry Blossom (2016) is used as the primary text while exploring varieties of literary and documentary works, presenting the Hiroshima traumatic events: John Hersey’s Hiroshima (1946), Richard H. Minear’s Hiroshima: Three Witnesses (1990) —focusing on only two witnesses Hara Tamiki and Ōta Yōko— and Steven Okazaki’s White Light/Black Rain: The Destruction of Hiroshima and Nagasaki (2007). Each work differs in genre, narrative, style, and retelling of the nuclear catastrophe while covering a wide spectrum of literary presentations of historical trauma. The thesis compares the different narrative strategies and depictions in relaying traumas to readers who have not experienced the event firsthand. Furthermore, it sheds light on the political agenda of the nuclear catastrophe in Hiroshima, and how it contributed to the trauma of the survivors.